MATHEMATICAL LITERACY REVIEWED FROM MATHEMATICAL PROBLEM SOLVING ABILITY (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2018)
This study is motivated by the importance of elementary school students' mathematical literacy skills in relation to 21st century education problems. This study aims to determine the mathematics literacy of fifth grade students in elementary school in terms of mathematical problem solving abilities. The research design used was qualitative descriptive with a case study research method. This study was carried out on 27 fifth grade students of one public elementary school in the city of Bandung. This research was carried out by observing and giving mathematics literacy tests. The results showed that students' mathematical literacy was still low. Accuracy in understanding the information in the questions about what was known and asked about the questions was lacking. Most students are still wrong when it comes to working on the calculation process and what procedures should be used to solve the given problem so that the results obtained are not correct. Based on these findings, learning needs to be designed to be as optimal as possible in order to improve mathematical literacy skills.